1996
DOI: 10.1111/j.1365-294x.1996.tb00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic introgression between native and introduced brown trout Salmo trutta L. populations in the Rhone River Basin

Abstract: In the Doubs River (Rh6ne drainage) two distinct brown trout (S. tnrtta) phenotypes are observed. One phenotype is locally called Doubs trout and is characterized by four black stripes on the sides, similar to perch (Perca fluviatilis L.) and the other i s the common phenotype of the fluviatile ecotype of brown trout, Salmo tnrtti f. firio. Protein data for three samples from the Doubs show that the Doubs trout belongs to the Mediterranean population group of brown trout, whereas the fario phenotype originates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 27 publications
5
96
0
1
Order By: Relevance
“…Une étude génétique (LARGIADER et SCHOLL, 1996) a montré que la truite autochtone du Doubs appartient au rameau évolutif méditerranéen. Or la plupart des souches de repeuplement utilisées dans le Doubs franco-suisse jusque dans les années 90 étaient originaires de stocks domestiques de forme atlantique, même si une part limitée provenait de croisements entre des géniteurs atlantiques domestiques et des truites sauvages, le plus souvent mâles.…”
Section: Pratiques De Repeuplementunclassified
“…Une étude génétique (LARGIADER et SCHOLL, 1996) a montré que la truite autochtone du Doubs appartient au rameau évolutif méditerranéen. Or la plupart des souches de repeuplement utilisées dans le Doubs franco-suisse jusque dans les années 90 étaient originaires de stocks domestiques de forme atlantique, même si une part limitée provenait de croisements entre des géniteurs atlantiques domestiques et des truites sauvages, le plus souvent mâles.…”
Section: Pratiques De Repeuplementunclassified
“…Also pertinent is the exclusive presence of the LDH-A2*100QL allele in a tributary of the upper Rhone river (data in Largiadèr & Scholl, 1996), as discussed in greater detail below.…”
Section: Postglacial Spread Of Brown Trout 51mentioning
confidence: 99%
“…early emerging fry may be dominant to late emerging fry, therefore, the several days of difference between hatching times described by Álvarez and Garcia-Vazquez (2) might be crucial to establishing residence effects (2,39). it has been reported that hatchery and free-living brown trout can and do interbreed (13,18,21). in any case, a passive attitude towards the possible outcomes for the biodiversity is not a viable option.…”
Section: Resultsmentioning
confidence: 99%